Strategies for Pre-service Secondary English Teacher Development in the UK - Maski Rana, Karna Bahadur (Journal of NELTA, 2011)
The pre-service secondary English teacher development programmes in a university in the UK were selected for the analysis. The efficiency of Post-Graduate Certificate Examination (PGCE), School-Centred Initial Teacher Training (SCITT) and Graduate Teacher Programme (GTP) was analysed using the experiential and reflective knowledge of prospective teachers. The professional knowledge categories were 'learning theories in ITT', 'subject knowledge' and 'vocational practice in ITT'. Qualitatively significant coherence is found between the categories. The study suggests that an appreciation of learning theories is essential for English language teaching and provide a framework for application of teaching strategies. Indeed, subject knowledge and teaching strategies were viewed as core parts of ITT courses for secondary English teacher development. The link between theoretical learning and pedagogical application of those theories in vocational training is identified. Key words: Teacher development; Pre-service teachers; Profession; Personality Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 134-145 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4619